Cross-sectional and longitudinal assessment of arterial stiffening with age in European and Chinese populations - Wojciechowska, Wiktoria; Li, Yan; Stolarz-Skrzypek, Katarzyna; Kawecka-Jaszcz, Kalina; Staessen, Jan A.; Wang, Jiguang (Frontiers in Physiology, 2012)
As arteries become stiffer with ageing, reflected waves move faster and augment late systolic pressure. Few studies have described the age-related changes in both peripheral and central systolic blood pressures in populations. We investigated the age dependency of peripheral (pSBP) and central (cSBP) systolic pressure and pressure amplification (ie. difference between peripheral and central SBP) in randomly selected participants from European and Chinese populations. Data were collected in 1420 Europeans (mean age, 41.7 years) and 2044 (mean age, 45.1 years) Chinese. In cross-sectional analyses of the population samples cSBP consistently increased more with age than pSBP with the age-related increases being greater in women than men. Repeat assessment of pSBP and cSBP in 398 Europeans and 699 Chinese at a median interval approximately four years of follow-up confirmed that also within subjects cSBP rose steeper with ageing than pSBP. In conclusion, with ageing, pSBP approximates to cSBP. This might explain why in older subjects pSBP becomes the main predictor of cardiovascular complications.